Comparison of Vascular Invasion With Lymph Node Metastasis as a Prognostic Factor in Stage I-III Colon Cancer: An Observational Cohort Study - Bae, Jung Hoon; Kim, Ji Hoon; Kye, Bong-Hyeon; Al-Sawat, Abdullah; Lee, Chul Seung; Han, Seung-Rim; Lee, In Kyu; Lee, Sung Hak; Lee, Yoon Suk (Frontiers in Surgery, 2021)
Purpose: This study aimed to evaluate the prognostic impact of vascular invasion (VI) in comparison with that of lymph node metastasis (LNM) in non-metastatic colon cancer. Methods: Patients who underwent curative surgery for stage I-III colon cancer were divided into four groups depending on the status of VI and LNM (Group I: VI-/LNM-; Group II: VI+/LNM-; Group III: VI-/LNM+; Group IV: VI+/LNM+). Group III was subdivided according to the nodal (N) stage (Group IIIA: VI-/N1; Group IIIB: VI-/N2). Oncological outcomes were compared between Groups II and III. Results: In total, 793 non-metastatic colon cancer patients were included. Group II (hazard ratio [HR] 2.34, 1.01-5.41) and Group III (HR 1.91, 1.26-2.89) were independently associated with poor disease-free survival (DFS). The 5-year DFS rates were comparable in Groups II (71.6%) and III (72.5%) (P=0.637). When Group III was subdivided into Groups IIIA and IIIB, DFS deteriorated in the following order: Groups IIIA, II, and IIIB. The 5-year DFS rates were 79.7%, 71.6%, and 61.4% in Groups IIIA, II, and IIIB, respectively. Group II had a tendency toward early recurrence. The 1- and 2-year DFS rates were 76.3% and 71.6% in Group II and 88.3% and 79.8% in Group III, respectively (P = 0.067 and 0.247). All recurrences in Group II were distant metastases. Conclusion: VI is a prognostic factor as significant as LNM and may be a stronger prognostic factor than N1 stage in non-metastatic colon cancer. Furthermore, a potential association was observed between VI and recurrence patterns, such as early recurrence and distant metastasis.